Performance or Pleasure: Which Counts More for Virtual-Influencer Adoption in Indonesia? Kinerja atau Kenikmatan: Mana yang Lebih Penting dalam Penerapan Influencer Virtual di Indonesia? - Agung Stefanus Kembau; Christian Haposan Pangaribuan; Arief Perdana Kumaat; Devi Yurisca Bernanda; Fidelia Novena Doa (Universitas Muhammadiyah Sidoarjo, 2025)
In mobile-first collectivistic markets such as Indonesia, research has not yet clarified how consumers respond to virtual influencers (VIs), AI-driven characters that sell, entertain, and chat in parasocial spaces. Filling this gap is important because Indonesia is projected to become Asia’s fastest-growing e-commerce arena, valued at roughly ninety-five billion US dollars. We adapted the Artificial Intelligence Device Use Acceptance (AIDUA) model and surveyed 235 Instagram users aged 18 to 35 years who follow at least one VI. After pretesting, the final PLS-SEM model satisfied all reliability (CR ≥ 0.89) and convergent validity (AVE ≥ 0.73) thresholds and explained 37 percent of the variance in willingness to accept VIs. Positive emotion emerged as the strongest driver (β = 0.51, p < 0.001). Performance expectancy showed both a direct effect (β = 0.12, p < 0.05) and an indirect effect through emotion, whereas effort expectancy influenced acceptance solely through emotion. Perceived risk and social influence were not significant, confirming that feeling rather than function guides VI persuasion among young Indonesians. Brands should therefore pair clear decision support cues with local humor, everyday Bahasa, and low-friction interfaces to spark joy and reduce novelty skepticism, a strategy likely to accelerate VI adoption in other collectivistic mobile-centric economies.